Homologation chemistry with nucleophilic α-substituted organometallic reagents: chemocontrol, new concepts and (solved) challenges. Issue 50 (31st May 2018) - Castoldi, Laura; Monticelli, Serena; Senatore, Raffaele; Ielo, Laura; Pace, Vittorio
Abstract : The transfer of a reactive nucleophilic CH2 X unit into a preformed bond enables the introduction of a fragment featuring the exact and desired degree of functionalization through a single synthetic operation. Abstract : The transfer of a reactive nucleophilic CH2 X unit into a preformed bond enables the introduction of a fragment featuring the exact and desired degree of functionalization through a single synthetic operation. The instability of metallated α-organometallic species often poses serious questions regarding the practicability of using this conceptually intuitive and simple approach for forming C–C or C–heteroatom bonds. A deep understanding of processes regulating the formation of these nucleophiles is a precious source of inspiration not only for successfully applying theoretically feasible transformations ( i.e. determining how to employ a given reagent), but also for designing new reactions which ultimately lead to the introduction of molecular complexity via short experimental sequences.